2019
DOI: 10.4236/psych.2019.103022
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Self-Regulation Strategy Inventory—Self-Report (SRSI-SR)

Abstract: This work presents a systematic review of the Self-Regulation Strategy Inventory-Self Report (SRSI-SR). Theoretically grounded in Zimmerman's three-phase model of self-regulated learning (SRL), the SRSI-SR provides information about learners' use of three broad types of self-regulation strategies. Google Scholar, PsycINFO, and ProQuest were searched to identify studies referencing the SRSI-SR; 18 studies met the inclusion criteria. Studies were coded based upon: 1) Likert scale type employed, 2) type of study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Three factors were yielded from the confirmatory factor analysis: seeking/learning information (8 items: α = 0.84), environment and behavior management (12 items: α = 0.88), and maladaptive regulatory behaviors (8 items: α = 0.72). A systematic review of Cleary (2006) SRSI-SR questionnaire conducted by Tise et al (2019), which includes 18 studies and covered various disciplines (science, biology, history, math, English-language learning, and reading) highlights that overall reliability for the SRSI-SR among these studies is high, with Cronbach's alpha value ranging from 0.82 to 0.92. The internal consistency of this scale was also reported to be high (0.82) for the study in English language learning.…”
Section: Questionnaire Of Self-regulated Learning Strategies In Learn...mentioning
confidence: 99%
“…Three factors were yielded from the confirmatory factor analysis: seeking/learning information (8 items: α = 0.84), environment and behavior management (12 items: α = 0.88), and maladaptive regulatory behaviors (8 items: α = 0.72). A systematic review of Cleary (2006) SRSI-SR questionnaire conducted by Tise et al (2019), which includes 18 studies and covered various disciplines (science, biology, history, math, English-language learning, and reading) highlights that overall reliability for the SRSI-SR among these studies is high, with Cronbach's alpha value ranging from 0.82 to 0.92. The internal consistency of this scale was also reported to be high (0.82) for the study in English language learning.…”
Section: Questionnaire Of Self-regulated Learning Strategies In Learn...mentioning
confidence: 99%
“…Given that greater specificity in the SRL assessment process can enhance school-based practitioners' ability to link SRL assessment data to intervention planning, the current paper expands and updates the original SREP diagnostic model in several ways. In addition to providing more detailed information about the operation and sequence of the SREP assessment process, the current paper provides evidence supporting the utility and psychometric rigor of specific tools emphasized within the SREP diagnostic framework (e.g., self-report questionnaires, teacher rating scales, SRL microanalysis, think-aloud protocols; Cleary et al, 2021;Tise et al, 2019). This paper also serves as a roadmap that school psychologists can use to increase the frequency and quality of school-based SRL assessments.…”
Section: Introductionmentioning
confidence: 68%
“…It has also been adapted for postsecondary populations (Follmer & Sperling, 2016; Thomas et al, 2020), translated into multiple languages, and applied to different learning environments (e.g., in‐person vs. online; Khodarahmi & Zarrinabadi, 2015; Madjar et al, 2011; Zambrano et al, 2018). In terms of psychometric characteristics, there is evidence to support the reliability of scores and the validity of inferences regarding internal factor structure, and convergent and predictive validity (Cleary, 2006; Cleary et al, 2015; Tise et al, 2019). Although less attention has focused on the SRSI‐PRS and SRSI‐TRS, research has revealed similar levels of strong psychometric quality (Chen et al, 2015; Cleary & Callan, 2014).…”
Section: Srep—diagnostic Assessment Processmentioning
confidence: 99%
See 1 more Smart Citation